Patient Perceptions Regarding Clinical Follow-Up After Total Joint Arthroplasty - Jeremy S. Frederick, MD; Samuel D. Mounce, MD; Jeffrey A. Chapek, MD; Caitlin E. Conley, PhD; Stephen T. Duncan, MD; David C. Landy, MD, PhD (Arthroplasty Today, 2025)
Background: While considerable variation exists regarding patient follow-up after total joint arthroplasty (TJA), little is known regarding patient perceptions. Given the increasing need to deliver cost-efficient care, rising importance of satisfaction scores, and lengthened commutes with market consolidation, understanding patient perceptions and their predictors is important. Methods: A convenience sample of 75 patients was surveyed from the waiting room of an academic arthroplasty practice serving a large geographic catchment area regarding clinic travel and TJA follow-up perceptions. The sample resembled an expected arthroplasty population with 63% women, 46% between 50 and 64 years of age, and 42% having TJA in the past 2 years. Results: Median clinic travel time was 30 minutes (interquartile range, 15-75 minutes) with 15% finding this burdensome and 17% having transportation reliability concerns. Overall, 97% believed TJA follow-up necessary and 94% that it was important to their overall satisfaction with TJA. Regarding initial follow-up, 74% preferred a 2-week in-person visit, though 9% preferred a nurse phone call, and 8% a virtual visit. Demographic factors were not associated with follow-up preferences, though there were strong associations between preference for an alternative follow-up method and both increasing travel time (P = .04) and transportation reliability concerns (P = .03). Conclusions: While most patients preferred 2-week in-person follow-up, one-fourth preferred an alternative. Increasing travel time and decreased transportation reliability were associated with alternative follow-up preference. As market consolidation increases, it is important that patients have appropriate access to care which may involve more flexible follow-up pathways.